2001
DOI: 10.1123/tsp.15.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Team Cohesion, Effort, and Objective Individual Performance of High School Basketball Players

Abstract: Previous research has demonstrated the relationship between high cohesion and optimal team performance. This study investigated the cohesion-individual performance relationship and examined expended effort as a mediator of that relationship. At the middle and end of the regular season, 41 male and 49 female varsity high school basketball players representing eight teams completed measures of group cohesion and perceived expended effort. At the same time intervals, the players’ game statistics were gathered, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
1
28
1
1
Order By: Relevance
“…Some of these consequences are noted in this research, such as game playing (Bray and Whaley, 2001; Heuzé et al, 2006), expectations of success (Leo et al, 2010a), or performance (Heuzé et al, 2006; Ramzaninezhad et al, 2009). Hence, it would be interesting to use cluster analysis to determine different cohesion and efficacy patterns in a specific sample.…”
Section: Introductionmentioning
confidence: 70%
“…Some of these consequences are noted in this research, such as game playing (Bray and Whaley, 2001; Heuzé et al, 2006), expectations of success (Leo et al, 2010a), or performance (Heuzé et al, 2006; Ramzaninezhad et al, 2009). Hence, it would be interesting to use cluster analysis to determine different cohesion and efficacy patterns in a specific sample.…”
Section: Introductionmentioning
confidence: 70%
“…Indeed, personal characteristics such as the age and the experience of the players seem to affect the cohesion. Younger athletes emphasize to the social relationships and friendships in the team characteristics that are connected to the social cohesion (Bray & Whaley, 2001;Bukowski, Newcomb, & Hartup,1996). Granito and Rainey (1998) concluded that the cohesion of school teams was higher than university teams.…”
Section: Gioldasis Aristotelis; Bekris Evangelos; Gissis Ioannis; Kommentioning
confidence: 99%
“…Elle pourrait, pour peu qu'elle soit mise en regard des perceptions d'effort jouant le rôle de médiateur de la relation cohésion-performance, être une mesure objective plus réaliste, permettant de mieux cerner cette relation. Des études se sont penchées sur les relations des trois variables que sont la cohésion, l'effort et la performance (e.g., Bray & Whaley, 2001 ;Prapavessis & Carron, 1997a). Bray et Whaley (2001), s'inspirant de Prapavessis et Carron (1997a), selon lesquels, les perceptions de cohésion sont positivement associées à l'effort, concluent que la cohésion permet de prédire la performance (en particulier la performance objective individuelle) et que l'effort peut être considéré comme médiateur de la relation cohésion-performance.…”
Section: L'effort Et La Relation Cohésion-performanceunclassified